Filamentous Basidiomycetes in the Clinical Laboratory - Brandt, Mary E. (Curr Fungal Infect Rep, 2013)
Filamentous basidiomycetes are difficult to identify in the clinical laboratory, mostly due to lack of sporulation, and their role as agents of fungal infection can be difficult to assess. More cases of infection with these agents are being reported as more laboratories gain proficiency with the recognition of their subtle morphologic features and the use of DNA-based methods for identification. Most infections occur in the respiratory tract and sinuses, although brain infection has been reported. Susceptibility testing suggests that these agents will respond well to azole drugs other than fluconazole.